Coordination modes of 2-mercapto-1, 3-benzothiazolate in gallium and indium complexes. Issue 9 (3rd May 2017) - Basiak, Dariusz; Ziemkowska, Wanda; Socha, Paweł; Dobrzycki, Łukasz; Ochal, Zbigniew; Pindelska, Edyta
Abstract: 2-Mercapto-1, 3-benzothiazole (mbztH) may act as a chelating or bridging ligand. In this study, reactions of mbztH with Me3 Ga and Me3 In were examined. The products were characterized by NMR spectroscopy, elemental analyses, melting point, and molecular weight determinations. Formation of mononuclear chelating complexes Me2 M(mbzt) (M = Ga, In) was observed in solutions. Crystallization of Me2 M(mbzt) yielded uncommon non-symmetrical dinuclear complexes Me4 M2 (mbzt)2, in which one metal is bonded to two sulfurs and the other to two nitrogens. Abstract :